Biochemical variability of venoms from individual European and Africanized honeybees ( Apis mellifera) - Schumacher, Michael J.; Schmidt, Justin O.; Egen, Ned B.; Dillon, Kathryn A. (Journal of allergy and clinical immunology, 1992)
To study biochemical differences between venom from individual honeybees, venom sacs from 103 European (EU) bees and 92 Africanized bees represeting 12 different colonies were dissected, and the dry weight (DW) of venom from each bee was determined. Venom from each of these bees was studied with isoelectric focusing and functional assays for phospholipase A 2 and melittin. Phospholipase concentrations in individual EU bee venoms varied between 1.8% and 27.4% (wt/wt). The melittin concentration in EU bee venom varied less and, on the average, was found to be much lower than previously reported. There was an eightfold to ninefold difference between lowest and highest venom sac DW contents, suggesting the possibility of highly variable venom delivery from bee stings. One EU bee contained >300 μg of venom, three times the recommended maintenance dose for venom immunotherapy. Isoelectric focusing also demonstrated large differences between individual bees, with respect to major and minor components of their venoms. Africanized bees contained significantly less venom but more phospholipase than did EU bees. Bee venoms from different colonies differed in their DW content and in their concentrations of phospholipase and melittin. The results are relevant to the uncertainty of responses from sting challenges and field stings in allergic patients and massive stinging attacks on normal subjects.